Peranan Suami Dalam Upaya Penanggulangan Kekurangan Energi Kronis (KEK) Ibu Hamil - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2004)
Abstract: Background: Since Indonesia suffered monetary crisis, the government program was Social Safeguard Net Program in the field of healthy for pregnant woman through Pemberian Makanan Tambahan Pemulihan (PMTP) program. Target of PMTP program is the chronic energy deficiency (CEO) of pregnant woman. The problem of PMTP program is not readiness of the family, which obtain PMTP program. However, pregnancy is not only woman responsibility, but also family responsibility especially the husband. Objective: The objective of research is to know the role of husband in order to overcome the CED of pregnant woman and to find some factors that affect the role of husband in order to overcome the CEO of pregnant woman. Methods: Research sample is the husband of pregnant woman, who suffered the CED in Puskesmas Salaman 1, Kecamatan Salaman, Kabupaten Magelang, Central Java. Research instrument is questionnaire to know knowledge, attitude, and action of the husband. Data collection method is to interview the husband and direct measurement of height, weight, and upper arm s circle of pregnant woman. Knowledge of husband is scored 1 (right) and 0 (wrong). Attitude of husband is scored 4 (very agree), 3 (agree), 2 (disagree) and 1 (very disagree). Action of husband is analyzed descriptively. Correlation and regression analysis with SPSS version 10 and SPS 2000 program are used to analysis data. Results and conclusion: The role of husband in order to overcome the CED of pregnant woman is shown by knowledge, attitude, and action. Knowledge of husband consist good knowledge 2.86%, intermediate knowledge 77.14% and bad knowledge 20.00%. Attitude of husband consist good attitude 97.14%, bad attitude 2.86% and intermediate attitude 0%. Actions of husband are example to deliver pregnancy checking